HZ. MUHAMMED'İN İBADETLERİ TOPLUMA BENİMSETME STRATEJİSİ - TUNÇ, TURĞUT (Fırat Üniveristesi, 2010)
Hz. Muhammed'in İbadetleri Topluma Benimsetme Stratejisi tolerans ve sabrı kapsamaktadır. Hiç eğitilmemiş ve gelişmemiş bir toplum bu strateji ile kısa süre içerisinde modern, uzlaşmacı ve tolerans sahibi bir topluma dönüşmüştür.Bu strateji muhatabın tüm karakteri ve davranışlarına dikkat ettiği için dinleyenlere daima inanılmaz bir şekilde etkilemiştir. Buna ilave olarak bu strateji puta inanma yerine doğru inancı bulmaya yardımcı olmuştur.Sonuç olarak İslam Hz. Muhammed'in bu stratejisi sayesinde bir dünya dini olmuştur. Bugün milyonlarca müntesibi bulunmaktadır.Anahtar kelimeler: Hz. Muhammed, İbadet, Strateji, Tolerans, Sabır, Din, Cahillik, İnanç.

The strategy of adopting the Prophet Muhammad?s worship to the puplic comprises the tolerance and the patience. Any uneducated and undeveloped puplic were easly changed to be very modern and very high level egreeable and tolerable puplic in a short time by means of this strategy. Since this strategy takes care of all the personalities and the bahaviours of the listeners, it always gives an unbelievable effect to them. Additionaly, it also helps these people to find the right beliefs instead of believing the idolater.In conclusion, the Islam becomes a world religion due to the strategy of the Prophet Muhammad and recently millions and millions people are still trying to be a member of this religion.Key Worlds: The Muhammad, Worship, Strategy, Tolerance, Patience, Religion, İgnorance, Belief.
The strategy of adopting the Prophet Muhammad?s worship to the puplic
Keywords: Din